ANALISIS PELAKSANAAN PROGRAMPOSPEMBINAAN TERPADUPENYAKIT TIDAK MENULAR DI WILAYAH KERJA PUSKEMAS SRONDOL KULON, KOTA SEMARANG (Studi Kasus di RW 13, Kecamatan Srondol Wetan, Kelurahan Banyumanik) - Irmawati, Refiola; Wigati, Putri Asmita; Arso, Septo Pawelas (Fakultas Kesehatan Masyarakat, 2018)
Integrated Development Center of Non-Communicable Diseases (Posbindu NCD) is a program that aims to increase community participation in prevention and earlydetectionofNCDriskfactorsthat implemented integratedly, routine and periodic. The target is all group of people aged 15thyears old and older. The participation of teenager to attend the Posbindu NCD Program is very low in Semarang. According to George C. Edward, there are four variables that determine the success of a policy, i.e. communication, resources, attitudes, and a bureaucratic structure. The purpose of this research is to analyze the implementation of Posbindu NCD program in Puskesmas Srondol Kulon, Semarang area. The research method is observational descriptive study with qualitative approach through in-depth interviews. This research was conducted in July 2017. The results of this research showed that Posbindu NCD program in Puskesmas Srondol Kulon is not implemented. Referring from communication variable, communication has not been made to all program objectives and incorrect information that makes miss understanding of the Posbindu’s target. The quantity of Human Resource to implement Posbindu program has fulfilled the requirements, but they lack of specific expertise for checking up the participants. Posbindu PTM only use the existing facilities, other supporting equipment bought with self-financing money. There are no SOP forPosbinduNCDimplementation, butthere is already a division with each task and responsibles to implementthePosbinduNCD program.